The Effectiveness Of Corporate Governance Code Revisions: The International Evidence - Ooi, Chai Aun (2018)
The literature lacks empirical evidence to show the effectiveness of progressive revisions on the national codes of corporate governance. Using firm-level data from 35 countries, this study shows that progressive corporate governance code revisions have significantly moderated the relationship between corporate governance score and firm value. Majority of the countries selected in this study has at least more than one code revision covered as the use of a panel data covering the years from 2007 to 2014. In detail, this study assesses corporate governance code revisions from three perspectives, i.e. the cumulative number of corporate governance code revisions, the number of new governance practices released in each revision, and the years of compliance with the codes.